PERSEPSI EKONOMI ISLAM MASYARAKAT TERHADAP RENCANA PENGAMBILAN KEBIJAKAN PROYEK KRL SIDOARJO-SURABAYA - Hidayat, Apriliyah Sasmita; Sa’adah, Mazro’atus (An Nawawi, 2024)
The Sidoarjo-Surabaya Electric Railway (KRL) project is aimed at improving connectivity and stimulating local economic growth. This study examines the economic perception of the project from an Islamic perspective and its alignment with the principles of Maqashid Sharia. The project is expected to create fair and sustainable economic benefits for the communities involved. The research finds that community support for the project is influenced by their involvement in decision-making processes, their perception of economic advantages, and the project's adherence to principles of social justice and environmental sustainability. In conclusion, the study emphasizes the importance of inclusive policies that prioritize economic justice. The project should not be solely considered a transportation solution, but also a catalyst for community prosperity in a sustainable manner.